Keys to basic schoolteacher training in the face of the social problems of the 21st century. Pedagogical models and policy proposals - Fizeshi, Oktaviia; ОkolnychaTetiana; Zhyhora, Iryna; Tsukanova, Nataliia; Shevtsova, Olena (Interacción y Perspectiva, 2025)
Emerging global concerns, such as unemployment resulting from automation, the digital divide and the challenges associated with migration, require rethinking the meaning and application of pedagogical models in basic education. In this scenario, the teacher becomes an agent of social transformation, whose work goes far beyond the simple transmission of content, involving decisions with profound political and social implications. The objective of this work was to critically discuss the material, ethical and epistemological keys that shape teacher training, understanding the teacher as an actor immersed in social problems that directly affect the teaching- learning processes. For this purpose, a hermeneutic and documentary methodology was used, selecting academic sources of recognized prestige and current relevance. The findings show that the pretended educational neutrality perpetuates existing inequalities and favors the status quo. Therefore, it is recommended that teacher training should incorporate the analysis of historical cases in which education was used as a tool of domination, as well as experiences of pedagogical resistance. This perspective makes it possible to understand that educating always implies a political, ideological and social positioning, indispensable to face the challenges of the 21st century and build a fairer and more democratic school.